BMP2 gene is a direct target gene of miR-378 in cattle - MA, TENG-HE; LIU, GUAN-HUI; LIN, DONG-MEI; WANG, BIN; CHENG, LONG; SHI, YU-XIANG (The Indian Journal of Animal Sciences, 2017)
In this study, dual luciferase assay was emplyed to validate whether the BMP2 is a direct target gene of bovine miR-378. miR-378 mimics had extremely significant effects on the luciferase activity of wild BMP2 3’-UTR, but had no effect on the mutated BMP2 3’-UTR. Our result indicated BMP2 is a direct target gene of bovine miR-378.